Vaccination against RhoC induces long-lasting immune responses in patients with prostate cancer: results from a phase I/II clinical trial - Klaus Brasso; Martin Andreas Roder; Hans-Georg Rammensee; Per thor Straten; Cécile Gouttefangeas; Juliane Schuhmacher; Sonja Heidu; Torben Balchen; Jennifer Rebecca Richardson; Camilla Schmeltz; Jesper Sonne; Jonas Schweiker (Journal for ImmunoTherapy of Cancer)
Background Peptide-based vaccination is a rational option for immunotherapy of prostate cancer. In this first-in-man phase I/II study, we assessed the safety, tolerability and immunological impact of a synthetic long peptide vaccine targeting Ras homolog gene family member C (RhoC) in patients with prostate cancer. RhoC is a small GTPase overexpressed in advanced solid cancers, metastases and cancer stem cells.Methods Twenty-two patients who had previously undergone radical prostatectomy received subcutaneous injections of 0.1 mg of a single RhoC-derived 20mer peptide emulsified in Montanide ISA-51 every 2 weeks for the first six times, then five times every 4 weeks for a total treatment time of 30 weeks. The drug safety and vaccine-specific immune responses were assessed during treatment and thereafter within a 13-month follow-up period. Serum level of prostate-specific antigen was measured up to 26 months postvaccination.Results Most patients (18 of 21 evaluable) developed a strong CD4 T cell response against the vaccine, which lasted at least 10 months following the last vaccination. Three promiscuouslypresented HLA-class II epitopes were identified. Vaccine-specific CD4 T cells were polyfunctional and effector memory T cells that stably expressed PD-1 (CD279) and OX-40 (CD134), but not LAG-3 (CD223). One CD8 T cell response was detected in addition. The vaccine was well tolerated and no treatment-related adverse events of grade ≥3 were observed.Conclusion Targeting of RhoC induced a potent and long-lasting T cell immunity in the majority of the patients. The study demonstrates an excellent safety and tolerability profile. Vaccination against RhoC could potentially delay or prevent tumor recurrence and metastasis formation.Trial registration number NCT03199872.